SYSTEMATIC LITERATURE REVIEW: MATHEMATICAL CONNECTIONS THROUGH PROBLEMBASED LEARNING IN TERMS OF ADVERSITY QUOTIENT - Lilik Supono; Arief Agoestanto (JME (Journal of Mathematics Education), 2023)
Mathematical connection is a skill needed to understand mathematical concepts and relate them to formulas taught, once taught, applied in other subjects, and applied to the real world. Every student has differences in terms of mathematical connection ability. This is known as the Adversity Quotient (AQ). AQ is divided into three groups: Climbers, Campers, and Quitters. Apart from the AQ review, an appropriate learning model to improve students' mathematical connections is the Problem-Based Learning (PBL) model. PBL is a learning model related to everyday problems. This study aims to (1) determine the effect of AQ on mathematical connection skills in the PBL learning model and (2) determine the influence of AQ onmathematical connection skills. The discussion in this article uses the SLR (System Literature review) method searched from Google Scholar, Scimago Journal Rank, and Publish or Perish from 2013 to 2023. The results of this study get 22 relevant articles. Of the 24 articles studied, 14 concluded that mathematical connections are appropriate for PBL learning models, andeight concluded that AQ's effect on students' mathematical connections is proportional or directly proportional. Students with a good AQ will have good math connections.